2013
DOI: 10.1590/1516-4446-2012-0922
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of cognitive-behavioral therapy on the treatment of phobic disorders measured by functional neuroimaging techniques: a systematic review

Abstract: Objective: Functional neuroimaging techniques represent fundamental tools in the context of translational research integrating neurobiology, psychopathology, neuropsychology, and therapeutics. In addition, cognitive-behavioral therapy (CBT) has proven its efficacy in the treatment of anxiety disorders and may be useful in phobias. The literature has shown that feelings and behaviors are mediated by specific brain circuits, and changes in patterns of interaction should be associated with cerebral alterations. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Studies that compared the brain signals obtained before and after treatment have reported changes that are consistent with this model of emotion regulation in depression Dichter, Felder, & Smoski, 2010;Goldapple et al, 2004), phobic disorders (Almeida et al, 2013;Schienle, Schafer, Hermann, Rohrmann, & Vaitl, 2007;Straube, Glauer, Dilger, Mentzel, & Miltner, 2006), panic disorder (Beutel, Stark, Pan, Silbersweig, & Dietrich, 2010;Sakai et al, 2006), posttraumatic stress disorder (Lindauer et al, 2008;Thomaes et al, 2014), personality disorders (Schnell & Herpertz, 2007), and eating disorders (Vocks et al,2010;Vocks et al, 2011). In the treatment of depression, these studies have provided evidence that the neural correlate of psychotherapy may consist in increased activation of prefrontal areas when participants are exposed to emotional stimuli, representing successful recruitment of control processes in the context of emotion regulation (DeRubeis et al, 2008;Disner et al, 2011).…”
mentioning
confidence: 74%
“…Studies that compared the brain signals obtained before and after treatment have reported changes that are consistent with this model of emotion regulation in depression Dichter, Felder, & Smoski, 2010;Goldapple et al, 2004), phobic disorders (Almeida et al, 2013;Schienle, Schafer, Hermann, Rohrmann, & Vaitl, 2007;Straube, Glauer, Dilger, Mentzel, & Miltner, 2006), panic disorder (Beutel, Stark, Pan, Silbersweig, & Dietrich, 2010;Sakai et al, 2006), posttraumatic stress disorder (Lindauer et al, 2008;Thomaes et al, 2014), personality disorders (Schnell & Herpertz, 2007), and eating disorders (Vocks et al,2010;Vocks et al, 2011). In the treatment of depression, these studies have provided evidence that the neural correlate of psychotherapy may consist in increased activation of prefrontal areas when participants are exposed to emotional stimuli, representing successful recruitment of control processes in the context of emotion regulation (DeRubeis et al, 2008;Disner et al, 2011).…”
mentioning
confidence: 74%
“…Some published reviews observe brain CBT markers of efficacy, which usually involve the regulation of the activation of amygdala, insula, thalamus, the medial prefrontal cortex and hippocampus (Almeida et al, 2013;Porto et al, 2009). However, there are few studies that investigate the impact of CBT on cardiovascular parameters in anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, both intervention techniques showed their efficacy by producing a decrease in the activation of the brain areas associated with fear, although the brain regions activated were not the same, partially supporting the second hypothesis. Neuroimaging techniques provide neurobiological support for the efficacy of CBT in the treatment of phobic disorders [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%